Anesthesia Management for Epilepsy Surgery with Total Intravenous Anesthesia: A Case Report - Firdaus, Riyadh; Talitaputri, Clarissa Emiko (Jurnal Neuroanestesi Indonesia, 2025)
Background: Epilepsy is a neurological disorder characterized by recurrent seizures, affecting many aspects of life. Approximately 3040% of patients do not respond to antiepileptic medications, making surgery a crucial option. While only 1030% of these patients qualify for surgical intervention, procedures like temporal lobectomy are becoming more common. Anesthetic management is essential for intraoperative mapping of the epileptogenic focus. This case report discusses anesthetic strategies in elective epilepsy surgery. Case: A 55-year-old man with recurrent seizures was scheduled to undergo temporal lobectomy with amygdala-hippocampectomy. The patient was classified as American Society of Anesthesiologists (ASA) class 2 without sign of increased intracranial pressure and there was no plan to use intraoperative functional monitoring or intraoperative electroencephalogram by the surgeon, as the epileptogenic focus could be identified through previous functional magnetic resonance imaging (fMRI). The patient underwent general anesthesia with total intravenous anesthesia (TIVA) using a combination of propofol, remifentanil, and rocuronium. Depth of anesthesia was monitored using the Bispectral Index (BIS). There were no significant hemodynamic fluctuations intraoperatively, except for bradycardia during manipulation of the limbic system. The patient was extubated at the end of the operation and there were no seizures during postoperative monitoring. Conclusion: In epilepsy surgery, it is important to understand if intraoperative electrocorticography is planned, the impact of anesthetic drugs on epilepsy, brain protection management, hemodynamics, and early neurological function assessment postoperatively. The use of TIVA, along with adequate monitoring of the depth of anesthesia, is safe and beneficial for assessing neurological function early